PEMAHAMAN DAN PENGHAYATAN SIFAT DAN NILAI-NILAI PERKAWINAN KATOLIK DALAM KELUARGA - Fransisco Laga Wawin; Ola Rongan Wilhelmus (Lembaga Penelitian STKIP Widya Yuwana, 2026)
In the Catholic marriage, both husband and wife have an important role of maintaining the integrity of the marriage. Marriage does not always run smoothly according to the expectations of the Church and married couples. In the married life, husband and wife sometimes experience various challenges and problems related to the married life which can lead to divorce. The study aims to explore the nature and values ​​of Catholic marriage, and how far the values of Catholic marriage being integrated in everyday life. The research was done by using a qualitative method with a descriptive approach. Data were collected through direct individual interviews, and informants were selected purposively. The results of the study indicated that experiencing the nature and values ​​of Catholic marriage has a significant impact on the integrity of the marriage itself. However, married couples often experience several challenges such as marital disputes caused by economic factors, infidelity, excessive individualistic attitudes, and a decline in appreciation of the value of love between the couples. Responding to the challenges, married couples continue to strive of the integrity of their marriage by strengthening so called loyalty, a spirit of mutual love and a willingness to make sacrifices for the good of the family.